Effect of the combination of mexidol and diclofenac sodium on exudative inflammation in rats after ten-day preventive oral administration - E. A. Ivanova; A. G. Vasilchuk; A. I. Matyushkin; T. A. Voronina (Фармакокинетика и Фармакодинамика, 2022)
In rats with carrageenan-induced paw edema, diclofenac sodium significantly reduces exudation after ten-day preventive oral administration at a dose of 10 mg/kg but not 5 mg/kg. Mexidol at a dose of 100 mg/kg in combination with diclofenac sodium at a dose of 5 mg/kg (preventively orally, during 10 days, once a day) reduces paw edema during the first two out of four hours of its recording compared with the control group. However, ten-day preventive oral administration of mexidol at a dose of 100 mg/kg (once a day) increases the severity of carrageenan-induced paw edema in rats at four hours after the injection of the phlogogen.